2007
DOI: 10.1080/09603120601124280
|View full text |Cite
|
Sign up to set email alerts
|

Seaport as a source of hantavirus: A study on isolated isles

Abstract: Since small mammals from seaports have relative higher seroprevalences of hantavirus, this seroepidemiologic study was conducted on the isles in Kinmen and Lienchiang Counties along the coast of southern mainland China to determine whether seaport may play the role as a source of hantavirus. Among six species of small mammals trapped in Kinmen County, only male Mus musculus (6.7%) and Rattus losea (5.3%) were found to be positive. In Lienchiang County, five species of small mammals were trapped and positive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…R. norvegicus had not been found until 1970s in Xinjiang, and hantavirus antigens or hantavirus antibodies were only detected in the rats collected around railway stations in Xinjiang in 1980s [Zhang et al, 1992;A et al, 2001], in which HFRS has not been reported so far. Wu et al [2007] reported that seaport might be a source of hantavirus spread. Recently, it was found that the HFRS emerged in Bayannaoer district of Inner Mongolia might be caused by SEOV imported from the neighboring HFRS endemic areas [Zhang et al, 2009b].…”
Section: Discussionmentioning
confidence: 98%
“…R. norvegicus had not been found until 1970s in Xinjiang, and hantavirus antigens or hantavirus antibodies were only detected in the rats collected around railway stations in Xinjiang in 1980s [Zhang et al, 1992;A et al, 2001], in which HFRS has not been reported so far. Wu et al [2007] reported that seaport might be a source of hantavirus spread. Recently, it was found that the HFRS emerged in Bayannaoer district of Inner Mongolia might be caused by SEOV imported from the neighboring HFRS endemic areas [Zhang et al, 2009b].…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to its positive role in reducing the spread of HTNV-related disease, socioeconomic development can increase the risk for SEOV-related infection. For instance, urbanization and development of transportation systems can increase the frequency of migration for Norway rats, increasing the chances of contact with humans [15], [44]. Our previous research on the phylogenetic analysis of hantaviruses revealed three undefined lineages for SEOV and an SEOV spillover event in Hubei.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Seaports are known to be a major source of rodent-borne illness. 33 The rainy season is coincident with rice field work in northern Vietnam, and rainfall is reported to be strongly associated with larval mite population in the lifecycle. 34 We think that this host–vector situation might explain the highest incidence of scrub typhus in this season.…”
Section: Discussionmentioning
confidence: 99%